Medical Iot Devices For Chronic Disease Management (International Journal of Environmental Sciences, 2025)
The forecasting of chronic illnesses is crucial within the healthcare sector. Early diagnosis of such diseases is vital. Significant advancements in technology have led to the generation of vast amounts of data in the field of computer science. The development of clinical information networks has resulted in the creation of numerous medical databases. The process of knowledge extraction and the management of extensive heterogeneous data sets has emerged as a prominent research domain, referred to as data mining. A thorough analysis of medical data facilitates the early detection of diseases, enhances patient care, and improves community services through the extensive data advancements in the biomedical and healthcare sectors. The extraction and management of knowledge from large heterogeneous data sets have become a significant area of research. Accurate health data processing aids in the early identification of diseases, patient care, and community services, driven by the growth of large data in biomedical and healthcare fields.